An Analysis of the Relation between Personality and the Attractiveness of Total Rewards Components - Vandenberghe, Christian; St-Onge, Sylvie; Robineau, Évelyne (Relations industrielles / Industrial Relations, 2008)
This study examines the links between personality and the relative attraction of various total rewards components. A survey approach is adopted, with 967 individuals completing a questionnaire. These individuals are currently employed. Results show that, after controlling for the effects of several demographic variables, “Big-Five” personality traits do affect individuals’ attraction to the following total rewards components: quality of work and of social relationships, development and career opportunities, variable pay, indirect pay, flexibility of working conditions, and prestige. Among Big-Five personality traits, openness to experience best predicts the relative importance employees give to the various total rewards components.